ʿUmān al-Majhūla - Phillips, Wendell (Maṭābiʿ Madkūr wa-Awlādihi, 1967)
Keywords: Récits de voyage -- Oman

Warlords of Oman - Allfree, P. S. (Hale, 1967)
The publication of Warlords of Oman in 1967 coincided with the first export of oil from Oman and the beginning of momentous change in a country that had been virtually closed to the outside world. Since then under the leadership of His Majesty, Sultan Qaboos, the development of the country and its people has been recognized as an international success story.The events recorded in this book describe a very different state of affairs in a part of the world about which little was known at the time. Very few books had been published when this book first appeared in print, and although much has been written since about Oman and the events set down in this book, it remains a classic of Arabian travel and experience. Full of lively descriptions of people and places, its pages abound with delightful scenes of local color, lively encounters, fascinating characters, and enthralling incidents.
Keywords: Récits de voyage -- Oman